OP59 Financing universal health coverage: effects of alternative tax structures on public health systems in 89 low- and middle-income countries. (2nd September 2014) - Reeves, A; Gourtsoyannis, Y; Basu, S; McCoy, D; McKee, M; Stuckler, D
Abstract : Background: Progressive realisation of universal health coverage is a widely accepted goal for the post-2015 Millennium Development Goals and the "Grand Convergence" of health envisioned by the Lancet's Commission on Investing in Health. Yet the means to pay for it is a subject of intense debate. We investigated how alternative tax systems affect the breadth, depth, and height of coverage by public health systems and associated child and maternal health outcomes. Methods: Cross-national fixed effects models were used to assess the relationships between tax revenue, tax systems, and health system coverage in 89 low- and middle-income countries from 1995–2011. Results: We identified tax revenue as a major statistical determinant of progress towards universal health coverage. Each $100 per capita per year of additional tax revenues corresponded to $9.86 yearly increase in government health spending (95% CI 3.92, 15.8). This association was particularly strong for taxes on capital gains, profits and income ($16.7, 95% CI 9.16–24.3), compared with those on goods and services (-$4.37, 95% CI -12.9, 4.11). In countries with low tax revenues (<$1000 per capita per year), an additional $100 tax revenue per year substantially increased the proportion of births attended by a skilled attendant by 6.74 percentage points (95% CI 0.87, 12.6) and the extent of health coverage by 11.4 percentage points (95% CI 5.51, 17.2). However, in contrast, $100 per capita increase in regressive forms of taxation, such as taxes on goods and services, which may reduce the ability of the poor to afford essential goods, was associated with higher rates of post-neonatal mortality by 0.17 (95% CI 0.065, 0.28), increases in infant mortality rate (1–5 years) by 0.18 per 1000 live births (95% CI 0.05, 0.32) and increases in under five mortality rate by 0.43 per 100, 000 population (95% CI 0.14, 0.72). Conclusion: Increasing domestic tax revenues is a key element of a strategy to achieving universal health coverage, particularly in countries with low tax bases. Pro-poor taxes on profits and capital gains appear to support expansion of health coverage without the adverse effects on health outcomes of higher taxes on goods and services.